Study on Numerical Simulation and Electromagnetic Scattering of Time-Invariant Freak Waves. (20th September 2022) - Han, Lichen; Wu, Gengkun; Liu, Bin
Abstract : The occurrence probability of freak waves is related to the sea wave spectrum. In this paper, different wave spectrums are used to simulate time-invariant three-dimensional freak waves. Freak waves that meet the international standards are generated at fixed time and location by adjusting the energy of the wavelets. We studied the occurrence probability of freak waves under the conditions of different wave spectrums, different wind speeds, and different modulation ratios and optimized the calculation speed of the model. Simulation data show that the difference in the shape of the wave spectrum affects the probability of freak waves occurrence. The model conforms to the Benjamin–Feir index (BFI), and the ratio of wave steepness to spectrum bandwidth is the key. In this paper, the Kirchhoff approximation theory is used to study the electromagnetic scattering (EM scattering) properties of freak waves on the large scale. We ideally calculate the Normalized Radar Cross-Section (NRCS) from the sea surface with freak waves, under different wind speeds and different grazing angles. The NRCS of freak waves is extremely low, and the increase of wind speed and the decrease of the grazing angle will make the detection of freak waves more difficult. The possibility of detection of freak waves is higher at high grazing angles (low incidence angles). The numerical simulations provide reference for engineering.